Same-sex marriage : a thoughtful approach to God's design for marriage - McDowell, Sean.; Stonestreet, John. (Grand Rapids, MI : Baker Books, 2014)
"Same-sex marriage is here, presenting unique challenges and opportunities. How do those who follow Christ faithfully answer the standard talking points for same-sex marriage? And how can they best articulate the case for one-man, one-woman marriage in everyday conversation? Sean McDowell and John Stonestreet believe a thoughtful approach to God's design for marriage is the answer to both questions. The key is not a contentious attitude towards those who believe in same-sex marriage, but a winsome perspective that is faithful to Christ, committed to truth and shaped by a love for God and others. Christians need to know that because Christ has risen, there is no such thing as "all hope is lost." They are still called to engage culture even if they are viewed as wrong, illegal and intolerant"--
Machine generated contents note: pt. 1 What Marriage Is and Why It Matters -- 1.What Just Happened to Our Culture? -- 2.Beyond the Noise, Beyond the Heat: Starting at the Right Place -- 3.What Is Marriage? Part One: What God Thinks -- 4.What Is Marriage? Part Two: Leaving God Out of It -- 5.What Is Marriage? Part Three: The Tale of Two Definitions -- 6.The "Cosmological" Shift: How Same-Sex Marriage Got Here -- pt. 2 What We Can Do for Marriage -- 7.This Is No Time for Escape and Christianity Is No Excuse -- 8.Learning from the Past: A Movement Worth Examining -- 9.First Things First: The Call to Repentance -- 10.The Church and Same-Sex Marriage: A To-Do List -- 11.Giving Marriage Back to the World: Suggestions for the Long Haul -- 12.So, What Now?: Guidance for Everyday Questions.
Keywords: Same-sex marriage -- Religious aspects -- Christianity